2020
DOI: 10.3390/nu12123650
|View full text |Cite
|
Sign up to set email alerts
|

High Fat Rodent Models of Type 2 Diabetes: From Rodent to Human

Abstract: Poor dietary habits contribute to increased incidences of obesity and related co-morbidities, such as type 2 diabetes (T2D). The biological, genetic, and pathological implications of T2D, are commonly investigated using animal models induced by a dietary intervention. In spite of significant research contributions, animal models have limitations regarding the translation to human pathology, which leads to questioning their clinical relevance. Important considerations include diet-specific effects on whole orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 102 publications
2
22
0
1
Order By: Relevance
“…Although it is too early to conclusively resolve these discrepancies, it is possible to speculate that HFD in animal models does not fully mimic the human T2DM pathogenesis. This condition is a significant obstacle hampering translational studies on brain dysfunction in T2DM patients [266]. Amid these findings, understanding microglial activity in hypothalamic inflammation and its impact on metabolic diseases and aging will be beneficial in microglial research for designing successful treatment techniques.…”
Section: Cellular Contribution To Hypothalamic Inflammation a Microgliamentioning
confidence: 99%
“…Although it is too early to conclusively resolve these discrepancies, it is possible to speculate that HFD in animal models does not fully mimic the human T2DM pathogenesis. This condition is a significant obstacle hampering translational studies on brain dysfunction in T2DM patients [266]. Amid these findings, understanding microglial activity in hypothalamic inflammation and its impact on metabolic diseases and aging will be beneficial in microglial research for designing successful treatment techniques.…”
Section: Cellular Contribution To Hypothalamic Inflammation a Microgliamentioning
confidence: 99%
“…Insulin resistance, one of the critical characteristics of type 2 diabetes, is triggered by a high carbohydrate and fat diet. Low-dose STZ injections can cause a modest decrease in insulin production, similar to the latter stages of type 2 diabetes (Stott and Marino, 2020). However, the benefit of phytochemical tannin treatment on hyperglycemia and body weight in the DNP animal model is equivocal, with findings varying depending on the rat species, types of diabetes, DNP induction techniques, and substances delivery procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with phytochemical tannins has also been shown to help with DNP hyperalgesia and allodynia symptoms. Its anti-inflammatory, antioxidant, and antihyperalgesic properties are thought to be the mechanism for decreasing these symptoms ( Stott and Marino, 2020 ). According to Abo-Salem et al (2020) , treatment with EGCG alleviated hyperalgesia responses indicated by a hot plate, tail immersion, formalin, and carrageenan-induced oedema tests in STZ-induced diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance and hyperinsulinemia were reported to facilitate fat storing during the fattening period and be reversible during hibernation period [38]. The rapid and dramatic increase of body fat mass generally lead to the metabolic diseases, such as diabetes mellitus and atherosclerosis in laboratory rodents [39]; however, no atherosclerotic changes were found despite highly elevated plasma lipids in bear and ground squirrels [40][41]. Recently, the candidate noncoding cis elements that regulates hibernator fattening were identified by comparative phylogenomics [42].…”
Section: Resistance Against Metabolic Diseasesmentioning
confidence: 99%